Online Sales Activities Conducted by Adults and Involving Children in the Perspective of Positive Law in Indonesia - Silvia Rahmadhani Arsyad; Leni Widi Mulyani (Ilomata International Journal of Social Science, 2026)
The development of digital technology in Indonesia has significantly influenced social life and economic activities. One growing phenomenon is the involvement of children in digital-based commercial activities, such as social media content creation, live-streaming sales, and online product endorsements. While these activities offer economic opportunities and creative expression, they also pose serious legal risks, particularly concerning the protection of children from economic and psychological exploitation. Normatively, child protection in Indonesia is regulated under Law No. 35 of 2014 on Child Protection, Law No. 11 of 2008 in conjunction with Law No. 19 of 2016 on Electronic Information and Transactions, and Law No. 21 of 2007 on the Eradication of Human Trafficking. However, these regulations do not specifically address children’s involvement in digital commercial activities. This research employs an empirical juridical method by combining statutory analysis with field data obtained through interviews and observations involving parents, legal practitioners, and child protection institutions. The findings indicate that the absence of specific regulations governing digital child protection, along with weak supervision, increases the risk of economic and psychological exploitation of children. The novelty of this study lies in examining the relationship between Indonesian positive law and the practical realities of children’s participation in digital commerce. This research recommends the establishment of specific legal regulations, the strengthening of parental supervision, and increased accountability of digital platforms to ensure effective protection of children’s rights in the digital era.